Preparation method of silica gel and thermosol composite material

Through the uniform dispersion mixing and laminated pouring process of silicone and hot sol, composite materials with good wear resistance and flame retardancy are prepared, which solves the problems of poor wear resistance and poor flame retardancy of automotive interior materials and is suitable for substitution Genuine and imitation leather materials.

CN119217615AInactive Publication Date: 2024-12-31SHENZHEN LAIMEISI SILICON IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411323261.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing automotive interior materials have poor wear resistance and poor flame retardancy. The environmental pollution of genuine leather products is severe and expensive, making it difficult to meet the needs of high-end grades. At the same time, imitation leather materials have shortcomings in durability and wear resistance.

Method used

By using the preparation method of silicone and hot sol composite materials, the silicone powder and hot sol are uniformly dispersed and mixed, and the laminated pouring process is carried out in the frame mold to form a multi-layer structural composite material to ensure uniform curing of the material and bubble removal. Improve material wear resistance and flame retardancy.

Benefits of technology

It achieves good wear resistance, light scattering and flame retardant of composite materials, improves the strength and durability of the material, solves the problems of uneven dissolution of silicone and bubbles, and is suitable for alternatives to automotive interior materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217615A_ABST
    Figure CN119217615A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a silica gel and hot-melt adhesive composite material, and relates to the field of composite material preparation, and the preparation method comprises the following steps: S1, selecting proper silica gel and hot-melt adhesive, crushing the silica gel into powder, heating and dissolving the hot-melt adhesive, and dividing into three parts which are respectively marked as No.1, No.2 and No.3 for later use; s2, pouring silica gel powder into the second hot melt adhesive liquid, and stirring and mixing until the silica gel powder is uniformly dispersed into the second hot melt adhesive liquid. The composite material prepared from the silica gel and the thermosol has good wear resistance, light scattering performance and flame retardance, and in the process, the silica gel powder and the thermosol are dispersed and mixed uniformly, so that the problems that the silica gel is not easy to dissolve and is not uniformly mixed are solved, the problem of bubbles in the silica gel is solved, and the service life of the silica gel is prolonged. The strength, wear resistance and other properties of the composite material are further improved, and the composite material is convenient for people to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation, and specifically relates to a method for preparing a silica gel and hot melt composite material. Background Art

[0002] Silica gel (Silica) is also known as silica gel. It is a highly active adsorption material and an amorphous substance with a chemical formula of mSiO2·nH2O. It does not react with any substance except strong alkali and hydrofluoric acid, is insoluble in water and any solvent, is non-toxic and tasteless, and has stable chemical properties. Various types of silica gel form different microporous structures due to their different manufacturing methods. The chemical composition and physical structure of silica gel determine that it has many characteristics that are difficult to replace by other similar materials: high adsorption performance, good thermal stability, stable chemical properties, and high mechanical strength.

[0003] Hot melt adhesive is the abbreviation of hot melt adhesive. It does not use any flux during production and application. It is non-toxic, odorless, and does not pollute the environment. It is known as "green adhesive" and is particularly suitable for use on continuous production lines. The ratio of hot melt adhesive mainly refers to the mixed adhesive of hot melt adhesive and polyethylene wax. The more the mixed adhesive, the higher the peel strength, which affects the packaging effect. Too much wax will cause the peel strength to be too low and the packaging will easily crack.

[0004] At present, with the rapid development of my country's economy, the demand for leather products is increasing, and the grade is getting higher and higher. Automotive interior leather has been widely used in the interior parts of passenger cars and transport vehicles. The best choice for automotive interior leather is genuine leather, but genuine leather seriously pollutes the environment during its own production process, and the heavy metal content is easily exceeded. The yield rate is low during the processing of interior parts, and its price is expensive, making it difficult for low- and medium-end passenger cars to accept it. In addition, people gradually pay attention to environmental protection. Today, when environmental protection, energy conservation and sustainable development are advocated, people have also begun to develop imitation leather fabrics to replace animal leather to avoid harm to wild animals and damage to the natural environment.

[0005] Artificial leather, also called imitation leather or rubber, is a general term for artificial materials such as PVC and PU. It is made of foamed or coated PVC and PU with various formulations on a textile or non-woven base. It can be processed according to different strength, wear resistance, cold resistance, color, gloss, pattern and other requirements. It has the characteristics of a wide variety of patterns, good waterproof performance, neat edges, high utilization rate and relatively low price compared to genuine leather. At present, non-woven fabrics and composite materials such as polyvinyl chloride and polyurethane are mainly used for car door panels, car seat fabrics, dashboards, car interior walls, car roofs, steering wheel covers and other parts. Existing car interiors have poor wear resistance and poor flame retardancy. Summary of the invention

[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a method for preparing a composite material of silica gel and hot melt adhesive, which effectively solves the problems raised in the background technology.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a composite material of silica gel and hot melt adhesive, comprising the following steps:

[0008] S1. Select appropriate silica gel and hot melt, crush the silica gel into powder, heat and dissolve the hot melt, and divide them into three parts, marked as No. 1, No. 2 and No. 3 respectively, for standby use;

[0009] S2, pouring the silica gel powder into the hot sol liquid No. 2, stirring and mixing, until the silica gel powder is evenly dispersed in the hot sol liquid No. 2, and the silica gel powder remains in a suspended state in the hot sol solution without precipitation, to obtain a mixed solution;

[0010] S3, setting a base fabric layer, placing a frame mold on the base fabric layer, and then pouring the No. 1 hot melt adhesive solution prepared in S1 into the frame mold, and the poured hot melt adhesive solution flows in the frame mold until the base fabric layer in the frame mold is completely covered. After pouring, wait for the hot melt adhesive solution in the frame mold to cool to a gelatinous state, but not completely solidified, to obtain a No. 1 hot melt adhesive layer;

[0011] S4, pouring the mixed solution in S2 into the mold frame and onto the No. 1 hot melt adhesive layer. The poured mixed solution and the No. 1 hot melt adhesive layer will cross-mix at the contact position, and the remaining mixed solution will flow on the surface of the No. 1 hot melt adhesive layer until the No. 1 hot melt adhesive layer is safely covered, and then wait for it to cool and set into a gelatinous state, but not completely solidified, to obtain a No. 2 mixed layer;

[0012] S5, pouring the No. 3 hot sol solution prepared in S1 into the frame mold, preliminarily mixing the No. 3 hot sol solution with the No. 2 mixed layer at the contact position, and the remaining hot sol easily flows on the surface of the No. 2 mixed layer until the No. 2 mixed layer is completely covered, and then waiting for the material in the frame to completely cool and solidify to obtain a composite material blank;

[0013] S6, taking the composite material blank out of the frame mold, and polishing its surface to make it smooth, so as to obtain a composite material finished product.

[0014] Preferably, the powder specification of the crushed silica gel in S1 is 1000-1500 mesh.

[0015] Preferably, the proportions of the No. 1 hot melt solution, the No. 2 hot melt solution and the No. 3 hot melt solution in S1 are 1:3:1 respectively.

[0016] Preferably, the thickness of the No. 1 hot melt adhesive layer is 0.1 cm, the thickness of the No. 2 mixed layer is 0.3 cm, and the thickness of the No. 3 hot melt adhesive layer is 0.1 cm.

[0017] Preferably, the No. 1 thermosol solution, the mixed solution and the No. 3 thermosol solution are all poured using a flow-through method.

[0018] Preferably, the base fabric layer is laid on a vibration table, and the interior of the vibration table is vibrated by a vibration motor.

[0019] Preferably, the inner surface of the frame mold is coated with a mold degumming agent, and the mold degumming agent is made of kerosene, toluene and ethyl acetate.

[0020] Technical effects and advantages of the present invention:

[0021] 1. The composite material prepared by the present invention using silica gel and hot sol through the above process has good wear resistance, light scattering and flame retardancy. In the process, silica gel powder and hot sol are dispersed and mixed to make silica gel and hot sol dispersed and mixed evenly, thereby solving the problem of silica gel being difficult to dissolve and uneven mixing, and solving the problem of bubbles in silica gel, thereby further improving the strength and wear resistance of the composite material and facilitating people's use. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The figures are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the drawings:

[0023] Figure 1 It is a schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION

[0024] The present invention provides Figure 1 The method for preparing a composite material of silica gel and hot melt adhesive includes the following steps:

[0025] S1. Choose appropriate silica gel and hot melt adhesive, crush the silica gel into powder, heat and dissolve the hot melt adhesive, and divide it into three parts, marked as No. 1, No. 2 and No. 3 for backup. The silica gel can be selected with good elasticity and durability, and the hot melt adhesive should be selected with good adhesion to the silica gel;

[0026] S2, pouring the silica gel powder into the hot sol liquid No. 2, stirring and mixing, until the silica gel powder is evenly dispersed in the hot sol liquid No. 2, and the silica gel powder remains in a suspended state in the hot sol solution without precipitation, to obtain a mixed solution;

[0027] S3, setting a base fabric layer, placing a frame mold on the base fabric layer, and then pouring the No. 1 hot melt adhesive solution prepared in S1 into the frame mold, and the poured hot melt adhesive solution flows in the frame mold until the base fabric layer in the frame mold is completely covered. After pouring, wait for the hot melt adhesive solution in the frame mold to cool to a gelatinous state, but not completely solidified, to obtain a No. 1 hot melt adhesive layer;

[0028] S4, pouring the mixed solution in S2 into the mold frame and onto the No. 1 hot melt adhesive layer. The poured mixed solution and the No. 1 hot melt adhesive layer will cross-mix at the contact position, and the remaining mixed solution will flow on the surface of the No. 1 hot melt adhesive layer until the No. 1 hot melt adhesive layer is safely covered, and then wait for it to cool and set into a gelatinous state, but not completely solidified, to obtain a No. 2 mixed layer;

[0029] S5, pouring the No. 3 hot sol solution prepared in S1 into the frame mold, preliminarily mixing the No. 3 hot sol solution with the No. 2 mixed layer at the contact position, and the remaining hot sol easily flows on the surface of the No. 2 mixed layer until the No. 2 mixed layer is completely covered, and then waiting for the material in the frame to completely cool and solidify to obtain a composite material blank;

[0030] S6, taking the composite material blank out of the frame mold, and polishing its surface to make it smooth, so as to obtain a composite material finished product.

[0031] Meanwhile, the powder specification of the crushed silica gel in S1 is 1500 mesh, which can make the particle size of the silica gel powder finer and facilitate the uniform dispersion of the silica gel powder into the hot melt solution.

[0032] In addition, the proportions of the No. 1 hot melt solution, the No. 2 hot melt solution and the No. 3 hot melt solution in S1 are 1:3:1 respectively.

[0033] In addition, the thickness of the No. 1 hot melt adhesive layer is 0.1 cm, the thickness of the No. 2 mixed layer is 0.3 cm, and the thickness of the No. 3 hot melt adhesive layer is 0.1 cm.

[0034] Furthermore, the No. 1 thermosol solution, the mixed solution and the No. 3 thermosol solution are all poured using a flow-through method, which can avoid the generation of bubbles in the solution.

[0035] In addition, the base fabric layer is laid on a vibration table, and the interior of the vibration table is vibrated by a vibration motor, which can further avoid the generation of bubbles in the solution.

[0036] It should also be noted that the inner surface of the frame mold is coated with a mold degumming agent, which is made of kerosene, toluene and ethyl acetate, so as to facilitate separation of the frame mold after production.

[0037] Working principle of the present invention: Through the above process, the composite material prepared by using silica gel and hot melt has good wear resistance, light scattering and flame retardancy, and in the process, by dispersing and mixing silica gel powder and hot melt, the silica gel and hot melt are dispersed and mixed evenly, which solves the problem of silica gel being difficult to dissolve and uneven mixing, and at the same time solves the problem of bubbles in silica gel, further improving the strength and wear resistance and other properties of the composite material, making it convenient for people to use.

[0038] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0039] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a composite material of silica gel and hot melt adhesive, characterized in that: The production steps include: S1. Select appropriate silica gel and hot melt, crush the silica gel into powder, heat and dissolve the hot melt, and divide them into three parts, marked as No. 1, No. 2 and No. 3 respectively, for standby use; S2, pouring the silica gel powder into the hot sol liquid No. 2, stirring and mixing, until the silica gel powder is evenly dispersed in the hot sol liquid No. 2, and the silica gel powder remains in a suspended state in the hot sol solution without precipitation, to obtain a mixed solution; S3, setting a base fabric layer, placing a frame mold on the base fabric layer, and then pouring the No. 1 hot melt adhesive solution prepared in S1 into the frame mold, and the poured hot melt adhesive solution flows in the frame mold until the base fabric layer in the frame mold is completely covered. After pouring, wait for the hot melt adhesive solution in the frame mold to cool to a gelatinous state, but not completely solidified, to obtain a No. 1 hot melt adhesive layer; S4, pouring the mixed solution in S2 into the mold frame and onto the No. 1 hot melt adhesive layer. The poured mixed solution and the No. 1 hot melt adhesive layer will cross-mix at the contact position, and the remaining mixed solution will flow on the surface of the No. 1 hot melt adhesive layer until the No. 1 hot melt adhesive layer is safely covered, and then wait for it to cool and set into a gelatinous state, but not completely solidified, to obtain a No. 2 mixed layer; S5, pouring the No. 3 hot sol solution prepared in S1 into the frame mold, preliminarily mixing the No. 3 hot sol solution with the No. 2 mixed layer at the contact position, and the remaining hot sol easily flows on the surface of the No. 2 mixed layer until the No. 2 mixed layer is completely covered, and then waiting for the material in the frame to completely cool and solidify to obtain a composite material blank; S6, taking the composite material blank out of the frame mold, and polishing its surface to make it smooth, so as to obtain a composite material finished product.

2. The method for preparing a composite material of silica gel and hot melt adhesive according to claim 1, characterized in that: The powder specification of the silica gel in S1 after crushing is 1000-1500 mesh.

3. The method for preparing a composite material of silica gel and hot melt adhesive according to claim 1, characterized in that: The proportions of the No. 1 hot melt solution, the No. 2 hot melt solution and the No. 3 hot melt solution in S1 are 1:3:1 respectively.

4. The method for preparing a composite material of silica gel and hot melt adhesive according to claim 1, characterized in that: The thickness of the No. 1 hot melt adhesive layer is 0.1 cm, the thickness of the No. 2 mixed layer is 0.3 cm, and the thickness of the No. 3 hot melt adhesive layer is 0.1 cm.

5. The method for preparing a composite material of silica gel and hot melt adhesive according to claim 1, characterized in that: The No. 1 thermosol solution, the mixed solution and the No. 3 thermosol solution are all poured using the flow-through method.

6. The method for preparing a composite material of silica gel and hot melt adhesive according to claim 1, characterized in that: The base fabric layer is laid on a vibration table, and the interior of the vibration table is vibrated by a vibration motor.

7. The method for preparing a composite material of silica gel and hot-sol adhesive according to claim 1, characterized in that: The inner surface of the frame mold is coated with a mold degumming agent, and the mold degumming agent is made of kerosene, toluene and ethyl acetate.